Hubungan HUBUNGAN ANTARA MINAT BACA SISWA DENGAN KEMAMPUAN MEMBACA SISWA DALAM BELAJAR BAHASA INGGRIS (PELAJARAN PADA KELAS DELAPAN SMP NEGERI 14 SURAKARTA TAHUN PELAJARAN 2024/2025): HUBUNGAN ANTARA MINAT BACA SISWA DENGAN KEMAMPUAN MEMBACA SISWA DALAM BELAJAR BAHASA INGGRIS (PELAJARAN PADA KELAS DELAPAN SMP NEGERI 14 SURAKARTA TAHUN PELAJARAN 2024/2025) - Vocalia, Tyas Renada; Handayani, Sri (English Education Department Slamet Riyadi University Surakarta, 2024)
The aimed of this research was to determine (1) Students’ interest in reading English ability of the Eight grade of SMP Negeri 14 Surakarta, (2) to find out the students’ reading ability of the eight grade of SMP N 14 Surakarta, and (3) to find out whether or not there is correlation of study between Students’ reading interest and students’ reading ability of students in grade Eight SMP Negeri 14 Surakarta in the Academic year 2024/2025. This researcher was conducted at the eight grade of SMP Negeri 14 Surakarta in the academic year 2024/2025. Researcher used quantitative methods with correlation techniques. The researcher give questionnaire to 30 participants in order to gather the data Students’ reading interest in learning reading English in a class. The questionnaire used consisted of 30 items. Then, to measure the ability reading students, this research used a reading test for students. In this researsh was used random sampling technjque to collect the data. In data analysis, students’ questionnaires were measured using a Likert Scale, and reading tests were measured using Suharsimi Arikunto’s categories reading achievement. The findings of this research indicate that there are positive about correlation of research between students’ reading interest and students’ reading English ability. It is proven by the results of calculation of ((rxy) 0.615) > rtable in the significant table 5% (0.374) and 1% (0.478). Then, it can be concluded that the alternative hypothesis (Ha) is therefore deemed to be accepted and the null hypothesis (Ho) is rejected. Therefore, in this research it can be concluded that there is a positive the correlation of research between students’ reading interest and students’ reading English ability. This means students’ reading interest has higher impact, the better students’ reading ability. Keywords : Reading Interest, Reading English Ability, Correlational Study